2023
DOI: 10.1037/tra0001314
|View full text |Cite
|
Sign up to set email alerts
|

Happiness during a mass trauma: Predicting happiness during the COVID-19 pandemic through function, stress, anxiety, and coping.

Abstract: Objective: This study identifies the psychological mechanism that predicts happiness in mass trauma times by testing a model that includes coping styles, anxiety, stress, and function. Method: The survey comprised 509 respondents who answered questions about their demographic characteristics and ranked their happiness, stress, anxiety, function, and coping strategies. Structural equation modeling was used to test the model's goodness-of-fit analysis. Results: The theoretical model was a good fit for predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…In a conducted study, it was found that dealing with the anxiety, stress, function and emotion focusing on them in a mass process such as COVID-19 may contribute to the prediction of happiness and that there may be a negative correlation between happiness and stress. 22 Therefore, the negative correlation we found between happiness and psychological distress as well anxiety is supported by the literature.…”
Section: Discussionsupporting
confidence: 85%
“…In a conducted study, it was found that dealing with the anxiety, stress, function and emotion focusing on them in a mass process such as COVID-19 may contribute to the prediction of happiness and that there may be a negative correlation between happiness and stress. 22 Therefore, the negative correlation we found between happiness and psychological distress as well anxiety is supported by the literature.…”
Section: Discussionsupporting
confidence: 85%
“…The research on COVID-19 mainly emphasizes associations between the pandemic and negative psychological responses ( Braun-Lewensohn et al, 2021 ; Levy and Cohen-Louck, 2021 ; López-Núñez et al, 2021 ). However, scholars have also identified positives outcomes of the COVID-19 pandemic and related lockdowns ( Mancini and Mears, 2010 ; Chen et al, 2021 ; Levy and Cohen-Louck, 2021 ; Stallard et al, 2021 ; Cohen-Louck and Levy, in printing ). COVID-19 hardships can lead to manifestations of mutual support and courage ( Yu et al, 2021 ), and for some people, COVID-19 has facilitated positive behavioral and cognitive changes, such as spiritual growth ( Stallard et al, 2021 ), greater appreciation of life, discovery and embracement of new possibilities, and has enables individual posttraumatic growth (PTG; Stallard et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With millions of people infected across 213 countries, COVID-19 has led (as of July 2022) to approximately 6.35 million deaths worldwide (1). Additionally, COVID-19 has caused an array of adverse effects on mental health, civil rights, and the economy (2)(3)(4)(5). Many countries implemented full or partial lockdowns, with some lockdowns having lasted for lengthy periods and restricted all non-essential internal movement.…”
Section: Introductionmentioning
confidence: 99%
“…The research on quarantine suggests that it is unpleasant for those who experience it because it may involve separation from loved ones, financial problems, uncertainty over the situation and emotional difficulties ( 8 , 11 , 12 ). Recent studies that examined the effects of COVID-19 quarantine show negative psychological effects, including post-traumatic stress symptoms (PTSD), anxiety, depression, general distress, fear associated with outdoor activities, confusion and anger ( 5 , 8 , 13 16 ). Also, the length of quarantine is associated with an increased prevalence of PTSD and depressive symptoms, which might last after quarantine ends ( 14 , 17 ).…”
Section: Introductionmentioning
confidence: 99%